Hubungan kebiasaan konsumsi kopi dengan kejadian prehipertensi pada mahasiswa preklinik Fakultas Kedokteran Universitas Palangka Raya - Kamilan, Sofya; Jelita, Helena; Ahmad, Farah Fauziyah Radhiyatulqalbi; Lestarisa, Trilianty; Kahanjak, Donna Novina (Fakultas Kedokteran Universitas Palangka Raya, 2024)
Over time, there is a decrease in body resistance in a number of individuals, leading to the emergence of health problems. A common phenomenon observed is hypertension, which is often referred to as